Use of SCRATCH in Learning Programming in Higher Education - Pérez-Narváez, Hamilton (2020)
In recent years, the term computational thinking and Scratch programming language have broken into the teaching stage, primarily at the level of elementary and high school education. However, there are no studies that support the use of Scratch language at a higher level, thus the aim of this research was the verification of the development of computational thinking among the students of the First Semester of the Computer Science Degree of the Central University of Ecuador based on the eight dimensions of computational thinking that are: identification of patterns, use of instructions, variables, sequence, operators, reuse, abstraction, operation and error detection. For this purpose, a quasi-experimental design with pre-test-post-test and intact groups was applied, with a quantitative, field approach with documentary support and explanatory level. Subsequently, the SPSS tool was used for the statistical analyzes, both for the calculation of the measures of central tendency and the standard deviation, as well as in the verification of the hypotheses by means of T tests and in the elaboration of statistical figures. The results obtained evidenced a greater development in the levels of computational thinking with the students of the First Semester of the Computer Science Career of the Central University of Ecuador who used Scratch.